Therefore this equation has no solution return to

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: (a) =2 [Solution] x + 2 x + 5x + 6 2 2x (b) = 4[Solution] x +1 x +1 Solution (a) 2 -x =2 x + 2 x + 5x + 6 The first step is to factor the denominators to get the LCD. © 2007 Paul Dawkins 68 http://tutorial.math.lamar.edu/terms.aspx College Algebra 2 -x = x + 2 ( x + 2 )( x + 3) So, the LCD is ( x + 2 ) ( x + 3) and we will need to avoid x = -2 and x = -3 so we don’t get division by zero. Here is the work for this problem. ö 2öæ -x ÷ ( x + 2 )( x + 3) ÷=ç è x + 2 ø ç ( x + 2 )( x + 3) ÷ è ø æ ( x + 2 )( x + 3) ç 2 ( x + 3) = - x 2x + 6 = -x 3 x = -6 x = -2 So, we get a “solution” that is in the list of numbers that we need to avoid so we don’t get division by zero and so we can’t use it as a solution. However, this is also the only possible solution. That is okay. This just means that this equation has no solution. [Return to Problems] (b) 2 2x = 4x +1 x +1 The LCD for this equation is x + 1 and we will need to avoid x = -1 so we don’t get division by zero. Here is the work for this equation. 2x ö æ2...
View Full Document

This note was uploaded on 06/06/2012 for the course ICT 4 taught by Professor Mrvinh during the Spring '12 term at Hanoi University of Technology.

Ask a homework question - tutors are online